Chestnut starch modification with dry heat treatment and addition of xanthan gum: Gelatinization, structural and functional properties. (March 2022) - Liu, Wenmeng; Zhang, Yutao; Wang, Rongrong; Li, Jinwang; Pan, Wentao; Zhang, Xiaowei; Xiao, Wenhao; Wen, Huiliang; Xie, Jianhua
Abstract: The effects of dry heat treatment and xanthan gum (XG) on the functional, gelatinization, and structural properties of chestnut starch (CS) were investigated. The results showed that the gelatinization viscosity including peak viscosity (PV), trough viscosity (TV), final viscosity (FV), and setback viscosity (SB), viscoelasticity, gel strength and hardness of CS decreased after dry heat treatment, which were negatively correlated with the treatment time, but positively correlated with the addition of XG. X-ray diffraction (XRD) showed that gelatinization would destroy the crystal structure of CS gel. Scanning electron microscopy (SEM) showed that CS gel structure got uniform with the combination of dry heat treatment and XG. In vitro digestibility results showed that dry heat treatment with XG addition significantly increased the content of resistant starch (RS) of CS compared to those by dry heat treatment or added XG alone. These results indicate that the combination of dry heat treatment and XG is a potential physical technology for preparing RS, which were beneficial to prevent the incidence of type-II diabetes. Graphical abstract: Image 1 Highlights: Xanthan gum (XG) played an important role in gel formation of chestnut starch (CS). Dry heat treatment and XG synergistically increased resistant starch content of CS. The combination of dry heat treatment and XG made CS microstructure more compact.